The spirit and the letter of music - Barbo, Matjaž (De musica disserenda, 2015)
The 19th century emphasised the opposition between musical text and its performance. It seems that in the contrast between the unseizable spirit common to all arts and the letter of musical text the old oppositions can be seen, deepened even more with the historical progress of the accentuation of the individualisation of musical work. The aesthetic normatives of musical work have put into force the apparent concept of self-regulative autonomy, which, however, demonstrates that music has perhaps never actually rejected an external referential system.